Characterization of Amorphous Ibrutinib Thermal Stability - Trunov, Dan; Ižovský, Jan; Beranek, Josef; Dammer, Ondřej; Šoóš, Miroslav (Organic process research & development, 2025)
The choice of method for drug amorphization depends on various factors, including the physicochemical properties of the active pharmaceutical ingredients, the desired formulation, and scalability requirements. It is often important to consider a combination of methods or the use of excipients to further enhance the stability and performance of the amorphous drug. This study presents a comparison of techniques including melt quench, hot melt extrusion, solvent evaporation, ball milling, and lyophilization used for the preparation of amorphous ibrutinib. The amorphous material was thoroughly investigated using numerous techniques to examine changes in the physicochemical properties, stability, and degradation pathways of the drug product. During the examination, the temperature was discovered to be a key parameter for controlling the solubility and permeability of ibrutinib, which is influenced by the presence of the degradation product. We found that this degradation product could potentially polymerize and increase the molecular weight. The quantity, polymerization rate, and structure of the impurity can be regulated by the temperature variation during the amorphization processes. Additionally, the molecular weight of the degradation product was determined using Zimm plot analysis, which appeared for the first time in the literature for molecules of this category.